2004
DOI: 10.1007/s00787-004-0423-x
|View full text |Cite
|
Sign up to set email alerts
|

Self-image, war psychotrauma and refugee status in adolescents

Abstract: The aim of this study was to assess how war psychotrauma, refugee status and other factors relate to self-image. Psychotherapeutic-psychiatric interview, the Offer Self-Image Questionnaire (OSIQ), questionnaires for measuring war stressors, posttraumatic stress reactions (PTS-reactions), depression and general data were administered. A total of 322 adolescents from Bosnia-Herzegovina and Croatia were included in the study. In 60.32% of the examinees, more than four war stressors were encountered. In 13.68% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…In an attempt to assess war trauma, refugee status and other factors related to self-awareness, Begovac (2004) studied a sample of children from Bosnia, Herzegovina and Croatia who suffered from war trauma. Results of this study showed that (60.32%) of the examinees had low level of self awareness, and (13.68%) of the participants in this study had psychological problems related to trauma.…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to assess war trauma, refugee status and other factors related to self-awareness, Begovac (2004) studied a sample of children from Bosnia, Herzegovina and Croatia who suffered from war trauma. Results of this study showed that (60.32%) of the examinees had low level of self awareness, and (13.68%) of the participants in this study had psychological problems related to trauma.…”
Section: Introductionmentioning
confidence: 99%
“…Self-perception of adolescent at-risk populations has been recently investigated in relation to numerous psychological processes, such as depression (Korhonen, Laukkanen, Peiponen, Lehtonen, & Viinamäki, 2001), suicidal ideation (Ç etin, 2001), adaptation to divorce (Dunlop, Burns, & Bermingham, 2001), eating disorders (Erkolahti, Ilonen, Saarijärvi, & Terho, 2003), and war-related psychotrauma (Begovac, Rudan, Begovac, Vidovic, & Majic, 2004). To our knowledge, the link between self-concept and dating violence experiences has never been explored insofar as adolescents at-risk, especially those involved in the child protection services (CPS), are concerned.…”
Section: Introductionmentioning
confidence: 99%
“…I found, for example, papers on PTSD and on endeavouring to predict posttraumatic stress symptoms after traffic accidents [19][20][21][22]; links between depressive symptoms, alcohol use and injury in traumatized adolescents [23]; the course of PTSD in adolescents and young adults [24]; exposure to trauma, posttraumatic stress and PTSD in female youths who offend [25]; PTSD and depression in refugee children [26]; self-image, war psychotrauma and refugee status in adolescents [27]; and family violence and its short and longer term psychosocial effects. Figure 1 (from Ref.…”
Section: Introductionmentioning
confidence: 99%